Snow White with the red hair. 7 - Akiduki, Sorata (Shojo beat manga., 2020)
"Shirayuki is an herbalist famous for her naturally bright-red hair, and the prince of Tanbarun wants her all to himself! The prince from the neighboring kingdom, Zen, rescues her from her plight, and thus begins their love story ... Finally rid of the Claw of the Sea, Shirayuki and company return to Clarines--just in time for Palace Exhibition Day, the one day the palace is open to the public. But as Zen, bedecked in fancy garb, performs his princely duties, Shirayuki realizes how wide the gap between them truly is."--Back cover